Effects of migratory status and habitat on the prevalence and intensity of infection by haemoparasites in passerines in eastern Spain - Rivera, J.; Barba, E.; Mestre, A.; Rueda, J.; Sasa, M.; Vera, P.; Monrós, J. S. (Animal Biodiversity and Conservation, 2013)
The Iberian peninsula is a suitable place to study the effects of migratory condition on the prevalence of blood parasites in avian communities as resident, local populations cohabit with migratory species and with abundant vector populations. In this study we examined the incidence of avian blood parasites in three localities in the Mediterranean region (east Spain), in relation to the migratory status of the species. We analyzed 333 blood smears from 11 avian species, and obtained an overall prevalence of 9.6%. The prevalence of parasites varied among the different species studied, although intensity of infection did not. Our results are discussed in terms of population dynamics and abundance of Diptera vectors able to transmit blood parasites to other birds.